Not by bread alone : social support in the new Russia - Caldwell, Melissa L., 1969- (University of California Press, 2004)
What Muscovites get in a soup kitchen run by the Christian Church of Moscow is something far more subtle and complex--if no less necessary and nourishing--than the food that feeds their hunger. In Not by Bread Alone, the first full-length ethnographic study of poverty and social welfare in the postsocialist world, Melissa L.